AL WAHDAH AL ISLAMIYAH: RADIKALISME DAN KOMITMEN KEBANGSAAN - Wakhid Sugiyarto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The religious social organization, Wahdah Islamiyah (WI), is a local Islamic movement with its headquarters in Makassar. It has been growing rapidly with its main activities in da’wah (teaching dissemination) and education. Through qualitative approach, WI can be considered as a radical concept due to its strict adherence to Qur’an and Sunnah in line with asalafusshalih conception, but is friendly with its surroundings and has never developed any worrying da’wah (teaching dissemination) like attacking and mocking other groups in public lectures or its self-managed radio. All of the members and supporters recognize misleading teachings through a long-term learning process. WI thoughtfully realizes that the main obstruction in da’wah is poor public communication with other Islamic groups of people who have different interpretations, conceptions, and movements. Improving the communication can create a better understanding and might bring about some help from others. WI prohibits any opposition to the government as long as the government doesn’t prohibit muslims from practicing their teachings. WI believes that jihad is the highest level of a muslim’s conviction, not referring to terrorism, but a pure sincerity in practicing the religious teachings. War is only one of the jihad actions. Jihad in war is obligatory when the context exists.